Hydrodynamic 2d model of the city centre hydrosystem of the city of Wrocław and its flood capacity analysis - Robert Jerzy Banasiak (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: Flood conveyance analysis of the Hydrosystem of the Wrocław City.